2012
DOI: 10.15395/mkb.v44n2.82
|View full text |Cite
|
Sign up to set email alerts
|

Skrining Gangguan Dengar pada Pekerja Salah Satu Pabrik Tekstil di Bandung

Abstract: AbstrakPabrik tekstil di Indonesia merupakan sumber devisa yang penting untuk negara karena jumlahnya yang cukup banyak. Para pekerja pabrik mempunyai risiko tinggi untuk terjadinya gangguan dengar. Bunyi dengan intensitas yang cukup kuat (>85 dB) dalam waktu yang cukup lama dapat menyebabkan hilangnya pendengaran, baik sementara maupun tetap. Bila hal ini tidak mendapatkan perhatian yang serius maka dapat mengakibatkan dampak yang tidak diinginkan. Hal ini tidak sesuai dengan tujuan pembangunan kesehatan bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
1
5
0
4
Order By: Relevance
“…Furthermore, all the subject ( 100%) did not apply noise protection device while they worked, it is added more risk for NIHL incident on machinists and his assistant. 13 The reality from data that most of the subject are active smoker, also aggravate risk for NIHL, its consistent with research by Saber Mohammadi that NIHL risk 9,06 times higher on smoker than non-smoker. 15 NIHL is sensor neural type of hearing disorder characterized by the dip in the frequency 4 kHz.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Furthermore, all the subject ( 100%) did not apply noise protection device while they worked, it is added more risk for NIHL incident on machinists and his assistant. 13 The reality from data that most of the subject are active smoker, also aggravate risk for NIHL, its consistent with research by Saber Mohammadi that NIHL risk 9,06 times higher on smoker than non-smoker. 15 NIHL is sensor neural type of hearing disorder characterized by the dip in the frequency 4 kHz.…”
Section: Discussionsupporting
confidence: 71%
“…10 On factory workers at Bandung, 43 from 109 employee (39,45%) has subjective complaint such as clogged ear, discharge from ear, hearing loss, and intermittent tinnitus, about 41% suffered NIHL. 13 Previous study on electronic factory by Hardini Tjan (2013) found 29 subjects (85,3 %) has subjective complaints which is the most common are chronic malaise, headache and tinnitus. 7 Even though in this study there was present of subjective complaints, but based on statistical analysis found that there was not significant correlation between work duration and subjective health complaints ( p>0,05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Gender can also affect the incidence of hearing loss, men have a 3 times greater risk than women to experience hearing loss due to noise. [7][8] The most duration of therapy was <6 times the therapy but it was obtained the results of therapy with audiometry examination again showed no progress or the same as the original condition. This shows that ear massage therapy is not effective to cure ear disorders.…”
Section: Discussionmentioning
confidence: 99%